THE CHANGING IN SKILLS OF POSTPARTUM MOTHER IN CARRY OUT UMBILICAL CORD CARE BEFORE AND AFTER GIVEN HEALTH EDUCATION - Sylvina Rahmawati; Rica Arieb Shintami; Ummi Haniek (NHM PRESS, 2021)
Umbilical cord care is the treatment of the umbilical cord until the cord dries and released spontaneously in infants. The low ability of mothers in the treatment of post partum cord care. The purpose of this study to analyze changes in the mother's ability to post partum cord care before and after health education. This type of research using pre-experimental methods, the approach to one group pre-test post-test. The sample is all post-partum mothers who have babies by 15 respondents. The independent variable is health education, the dependent variable in the post partum mother's ability to umbilical cord care. Data dikumpukan by performing pre-test counseling and then giving a demonstration, after the post-test was performed to assess the ability of the mother post partum after a given health education. Then tested using the Wilcoxonstatistic. The results showed that the majority of respondents who provided health education to change in the ability to perform the correct treatment of the umbilical cord as many as 14 people (93.33%), while 1 (6.67%) post-partum mothers who did not change. Wilcoxon test results by score observations on pre-test and post-test showed that the p-value (0.014) <α (0.05) which means H0 rejected and H1 accepted, meaning that there is a change in the mother's ability to post partum cord care right before and after health education. One of the efforts that all post-partum mothers are able to do the right cord care is the provision of education by using models or other visual aids are more applicable to further facilitate the understanding of society